Exercitium pietatis - Calvin's interpretation of the Lord's Prayer - W. H. Neuser (Acta Theologica)
This article examines Calvin’s interpretation of the Lord’s Prayer by scrutinising it in the successive editions of his Institutes, the 1537 Catechism, the 1542 Geneva Catechism, the short paraphrase for the Geneva liturgy (1542), the exegesis of the Lord’s Prayer in the 1555 commentary or harmony of the Gospels (Matthew, Mark and Luke), and his explanation of the questions and answers for the 43rd Sunday of the 1542 Geneva Catechism (c. 1563). These sources reveal that, in the texts prior to 1555, Calvin placed a dogmatic emphasis on the six petitions. Later he shifted his attention to the actual practice of prayer. Initially he tried to understand the correct theological meaning of the Lord’s Prayer; later he urged the person who prays to use it correctly. At the outset the theologian spoke, later he became the pastor of souls. A comparison of the various texts reveals that throughout his life Calvin endeavoured to enhance his understanding of the Lord’s Prayer and its meaning.